2019
DOI: 10.1155/2019/2519020
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Ergonomic Conditions at Work: Influence on the Probability of a Workplace Accident

Abstract: Today, the economic and social importance of occupational accidents is undeniable worldwide. Hence, research aimed at reducing this type of accident is considered a discipline of great interest for society in general. In this environment, working conditions play a fundamental role in the occurrence of accidents, and from their study, results can be obtained that provide information for decision-making that guarantee optimum conditions for the development of the employees' tasks. Organizing the conditions of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
9
0
2
Order By: Relevance
“…There is a wealth of literature showing the association between high quantitative workloads and high cognitive demands and occupational injury. [37][38][39] Our current study supports these findings to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…There is a wealth of literature showing the association between high quantitative workloads and high cognitive demands and occupational injury. [37][38][39] Our current study supports these findings to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…Ergonomic and psychological risk factors are known to be major causes of occupational injury and musculoskeletal pain [ 43 44 45 ]. We also found that the likelihood of injury and musculoskeletal pain increased with ergonomic and psychological risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors impacting area unit are heating, lighting, and ventilation. 35 Ergonomics include physical conditions such as temperature, ventilation, work environment pollution, heating, machinery safety, etc., as significant elements that have a major impact on employee performance and health. 36 Personal Protective Equipment (PPE): PPE is an essential and mandatory obligation every industry abides by.…”
Section: Ergonomics and Employee Performancementioning
confidence: 99%